Comparative study between liver biopsy and non-invasive biomarkers in assessment of hepatic fibrosis in children with chronic liver diseases - Ola Galal Behairy; Ola Samir El-Shimi; Naglaa Hamed Shalan (SpringerOpen, 2021)
Abstract Background Liver biopsy is the gold standard for detecting the degree of liver fibrosis; however, invasiveness constitutes its main limiting factor in clinical application, so we aimed to evaluate the non-invasive biomarker formulas (APRI and FIB-4) and their modified forms by BMI z-score (M-APRI, M-FIB-4, and B-AST) compared to liver biopsy in the assessment of liver fibrosis in children with chronic liver diseases. Two hundred children aged 6.3 ± 3.8 years (98 males, 102 females) with chronic liver diseases underwent liver biopsy. The stage of fibrosis was assessed according to the METAVIR system for all children, and the following non-invasive biomarker formulas were calculated: APRI, modified APRI (M-APRI: BMI z-score × APRI), Fibrosis-4 index (FIB-4), modified FIB-4 (M-FIB-4: BMI z-score × FIB-4), and B-AST (BMI z-score × AST). The best cutoff value was calculated to detect early fibrosis (F1-F2) from advanced liver fibrosis (F3-F4). Results There were positive correlations between all studied non-invasive biomarker models (APRI, FIB-4, M-APRI, M-FIB-4, B-AST) and fibrosis score as an increase in fibrosis score was associated with an increase in mean ± SD of all studied biomarker formulas. The best cutoff values of non-invasive biomarker models in the diagnosis of early fibrosis (F1-F2) were APRI > 0.96, M-APRI > 0.16, FIB-4 > 0.019, M-FIB-4 > 0.005, and B-AST > −8 with an area under the curve above 0.7 each, while the best cutoff values of non-invasive biomarker models (APRI, M-APRI, FIB-4, M-FIB-4, and B-AST) in the diagnosis of advanced liver fibrosis (F3-F4) were >1.96, >2.2, >0.045, and >0.015, >92.1, respectively, with an area under the curve above 0.8 each. Conclusion APRI, M-APRI, FIB-4, M-FIB-4, and B-AST are good non-invasive alternatives to liver biopsy in the detection of liver fibrosis in children with chronic liver diseases of different etiologies especially those that include BMI z-scores in their formulas.